(untitled) (American Journal of Islam and Society, 2013)
Modernity, Sexuality, and Ideology in Iran represents a significant moment in artistic resurrection and re-vision. It examines the life and work of a discarded Iranian female popular artist known as Shahrzad (b. 1946). Through critical attention previously denied to Shahrzad, Talattof honors her creative contributions and, by extension, recognizes and honors artists like her who have been marginalized for the last several decades, their art labeled as “shameful” or “profane” due to their unacceptable sexual roles as dancers, singers, and actresses. Through the lens of her life and legacy, he argues that true modernity can never fully emerge without space for the discussion of sexuality – especially that of women. The author takes a risk in offering critical analysis of this artist’s life and work, for Shahrazad is recognized neither in the canon, nor by the giants of committed literature in Iran, the dominant style when she was writing in the 1970s. While detailing and noting the significance of her accomplishments, he asks why she has not been so recognized and locates that question along a line of inquiry as regards Iran’s “missing” modernity. He asks why a nation with such a long tradition of the scientific and socio-cultural accomplishments seems suddenly stuck in a medieval mindset, selectively applying modernity in such a way that it serves only to fortify the establishment in its extreme policies – through such “modern” means as technology ...